IL-37 inhibits M1-like macrophage activation to ameliorate temporomandibular joint inflammation through the NLRP3 pathway. (17th May 2020) - Luo, Ping; Peng, Sisi; Yan, Yin; Ji, Ping; Xu, Jie
Abstract: Objectives: IL-37 has been identified as an important anti-inflammatory and immunosuppressive factor. This study was undertaken to explore how IL-37 affects M1/M2-like macrophage polarization and thus contributes to anti-inflammatory processes in the temporomandibular joint. Methods: Western blotting, quantitative real-time PCR (qRT-PCR) and immunofluorescence were used to verify the IL-37-induced polarization shift from the M1 phenotype to the M2 phenotype, and the related key pathways were analysed by western blotting. Human chondrocytes were stimulated with M1-conditioned medium (CM) or IL-37-pretreated M1-CM, and inflammatory cytokines were detected. siRNA-IL-1R8 and MCC-950 were used to investigate the mechanism underlying the anti-inflammatory effects of IL-37. Complete Freund's adjuvant-induced and disc perforation-induced inflammation models were used for in vivo studies. Haematoxylin and eosin, immunohistochemical and safranin-O staining protocols were used to analyse histological changes in the synovium and condyle. Results: Western blotting, qRT-PCR and immunofluorescence showed that IL-37 inhibited M1 marker expression and upregulated M2 marker expression. Western blotting and qRT-PCR showed that pretreatment with IL-37 suppressed inflammatory cytokine expression in chondrocytes. IL-37 inhibited the expression of NLRP3 and upregulated the expression of IL-1R8. Si-IL-1R8 and MCC-950 further confirmed that the anti-inflammatory properties of IL-37 were dependent on the presence of IL-1R8 and NLRP3. In vivo, IL-37 reduced synovial M1 marker expression and cartilage degeneration and increased M2 marker expression. Conclusion: IL-37 shifting of the polarization of macrophages from the pro-inflammatory M1 phenotype to the beneficial anti-inflammatory M2 phenotype seems to be a promising therapeutic strategy for treating temporomandibular joint inflammation.